Neurovascular Reactivity after Repeated Attacks in Patients with Multiple Sclerosis - Nevzat Uzuner; Gulnur Tekgol Uzuner (International Journal of Multiple Sclerosis and Related Disorders, 2017)
Objectives Increased neurovascular (NV) reactivity has been shown in patients with relapsing-remitting multiple sclerosis (RRMS) during the acute exacerbation period. However, the NV reactivity after several attacks is not known. We, therefore, have investigated the patients by transcranial Doppler (TCD) using simple visual stimulation after the repeated attack periods. Patients and Methods Thirty patients (22 females and eight males, mean age 40 years) with RRMS were examined at least two times. The average TCD examination interval was 26.7 months (range 4-120 months). Mean attack number was 3.8 (range 2-8 times), average disease duration was 57 months (range 4-124 months), and average Expanded Disability Status Scale (EDSS) value was 2.5 (range 1-5.5). We performed transcranial Doppler recordings from the P2-segments of both posterior cerebral arteries simultaneously during simple visual stimulation. The NV reactivity was defined as a relative increase of the blood flow velocities during visual stimulation. Results The NV reactivity to simple visual stimulation was significantly lower in the second test on both sides (31.5±9.2% and 29.2±7.2%; right and left side, respectively) from those of the first test (38.3±11.9% and 36.0±11.9%; right and left side, respectively) (p<0.001). Conclusion The present study is the first study examining neurovascular reactivity in patients with RRMS during repeated attacks using the transcranial Doppler to our best knowledge. Our results suggest patients with RRMS after repeated exacerbation periods have less reactive neurovascular units in the occipital cortex. The possible explanation might be the repeated demyelination, and insufficient remyelination with longer disease duration may lead glial dysfunction resulting neurovascular unit impairment. If so, functional TCD may be useful for the determining of the disease progression. However, the exact cut-off point is not known.
Keywords: Multiple sclerosis